PENGEMBANGAN MODUL AJAR IPAS TERINTEGRASI ACTIVE LEARNING DALAM MENINGKATKAN PRESTASI BELAJAR SISWA KELAS IV SEKOLAH DASAR - Devi Anggi Friani (STKIP Subang, 2024)
This study aims to develop an Active Learning-integrated teaching module for Science and Social Studies (IPAS) to enhance the learning outcomes of fourth-grade elementary school students. This research is a Research and Development (R&D) study using the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study are fourth-grade students in Magetan District. The research instruments include expert validation questionnaires, teacher and student response questionnaires, implementation observation sheets, and learning outcome tests (pre-test and post-test). The results show that the developed teaching module received an average validation score of 89% (highly feasible) from subject matter experts, media experts, and practitioner teachers. The practicality of the module, based on teacher (87%) and student (85%) responses, falls within the practical to very practical category, indicating that the module is easy to use in the learning process. The effectiveness of the module was also demonstrated by a significant improvement in students' average learning outcomes, from 66.4 (pre-test) to 83.7 (post-test), with paired t-test results showing a significant difference (p < 0.05) and an N-Gain score of 0.56, which is considered effective. Therefore, the Active Learning-integrated IPAS teaching module developed in this study is proven to be valid, practical, and effective in improving elementary school students' learning outcomes.